Perlindungan Hak Tersangka Dan Terdakwa: Penegakan Prinsip Fair Trial dalam Sistem Peradilan Pidana - Putu Sekarwangi Saraswati (Jurnal Hukum Saraswati, 2025)
The Unitary State of the Republic of Indonesia as a constitutional state (rechtstaat) based on Pancasila means that Pancasila is the source of all laws applicable in this country. All citizens within a constitutional state, without exception, are treated equally before the law (Equality Before The Law). They are entitled to recognition and human rights, whereby all people have the right to be treated equally. One of these rights is the right to a fair trial, which is an important part of human rights, recognized in both national and international law. In the 1945 Constitution itself, this is stated in Article 24 paragraph (1), which states that “Judicial power is an independent power to administer justice in order to uphold law and justice” and Article 28 D paragraph (1), which states that "everyone has the right to recognition, guarantees, protection, and legal certainty as well as equal treatment before the law." The research method used in this study is qualitative with a literature study approach. The results obtained from this study are that the rights of suspects and defendants must fulfill the principles of a fair trial in order to guarantee certainty and protection. The scientific contribution of this article is to provide an understanding of the protection of the rights of suspects and defendants in the principle of fair trial in the criminal justice system.